GERMINABILITY AND INITIAL DEVELOPMENT OF NEW INTRA-SPECIFIC HYBRIDS OF Theobroma cacao L - Chávez Giler, Joel (2020)
The objective of this research was to evaluate the germinability of seeds and the initial development of interclonal hybrids of Theobroma cacao L. The trial was established in the experimental campus "La Teodomira", Manabí, Ecuador. Intraspecific crosses were made between five genotypes of T. cacao, the fruits obtained were harvested at approximately 180 days. The variables studied were: germination and emergence percentage, plant height, stem diameter, number of leaves and chlorophyll content in the leaf area. A 97.8% germination was obtained at eight days after demulization and imbibition and an 86.5% emergence, registering a higher percentage of germination and emergence in the progeny derived from the L11-H19 x EET-103 cross. At 120 days, the greatest stem diameter was recorded in the EET-558 x CCN-5 family and the greatest height in the EET-103 x L11-H19 family. On average, 15 leaves per plant and 43.5 of SPAD chlorophyll were obtained at 120 days. The chlorophyll content in the leaves is determined by the physiological age of the seedlings. However, for future research it is recommended to carry out field evaluation of these progenies, especially of physiological aspects involved with the production of leaves and chlorophyll content, since these could be indicators for the selection of promising genotypes